Aplicações da geometria analítica na resolução de problemas - Lacerda, Assiclero Cavalcante Teotonio de (2015)
The present work it is a proposal of approach of Analytic Geometry to be used as a tool on resolution of problens in general. The Analitic Geometry has its greater value axacty where it is unespected, in aplications in other branches of exact ecience. The purpose it is to shou hom the Analytic Geometry can be applied, and hau ea we do to emplasize to students thal the Analytic Geometry is not a part of Matematics which ends itself. We will mak vector approach, when it is convinient making the statments in formulas and resolutions of problens, become more simple. We beliave that making a articulation between Analytic Geometry and its application, in a very natural way, we are improving, the level of students learning.